The assessment of NGOs as a tool of funding and accountability - Πετρόπουλος Σωτήρης (The Greek Review of Social Research, 2014)
In recent decades the concept of evaluation and its practical applications gradually expanded from the business world in many human activities. For example, since the 1980s, terms such as efficiency, management by objectives and finally evaluation have found increased application within the public sector and especially in the field of development assistance. As frequent recipients / managers of development funds, NGOs around the world have gradually infused in their operations evaluation techniques either at project or at organization and / or industry level. This tendency has been reinforced by the emergence of new donors as well as the enhanced public interest on the sector. All these developments seem to lead to the gradual creation of tendency to enhance evaluation procedures within the sector.